Development of Practicum Tools for Measuring Temperature and Air Humidity Based on Microcontroller by Telemetric - Muhammad Zaky; Nita Carolina; Unggul Unggul (Universitas Tadulako, 2023)
The purpose of this research is to make a temperature measuring instrument for air temperature and humidity on the device using the DHT11 sensor as a temperature and humidity sensor for the object under study, the ATMega328P CH340G microcontroller as data processing and the Bluetooth HC-05 module as an intermediary communication between the device and a smartphone. , utilizing App Inventor technology as a means of information quickly and accurately. The research method used in this study is the research and development method or known as research and development (R&D). This measuring tool is made using the Arduino Uno R3 module, which is programmed using the Arduino programming language. Based on the results of the study, it can be concluded that: 1) The measuring instrument is designed to be able to measure temperature and humidity in a place/room continuously, 2) the system can provide precise and accurate information on the temperature and humidity of the device to the user. The additional result is that apart from practical measuring tools it can also be used as a wireless monitoring tool for temperature and humidity for swiftlet houses which is useful for solving temperature and humidity problems in swiftlet houses as well as outputs of Intellectual Property Rights Products.